Preserving Institutional Memory Through Photographic Collections - Costa, Rosa da P. F. da; Oliveira, Thiago G. de; Föeger, Rayra da S.; Moraes, Margarete F. de (Farol, 2025)
This article aims to highlight the importance of photographic collections as a source of information for the preservation of institutional memory. Specific objectives include: defining memory and institutional memory in the field of Information Science and related areas; examining the history of photography and its aspects as a document of historical value and its relationship with institutional memory in the literature; and presenting the relevance of preserving photographic collections in institutions. Regarding methods, the research is characterized by a qualitative approach and is exploratory in nature, having conducted a literature review. It is concluded that photographic collections are extremely important for the preservation and dissemination of institutional memory, which is also part of the memory of all individuals involved, such as employees, suppliers, and clients. It is also observed that institutions need to pay more attention to the management of photographic collections, especially digital ones, which are often disorganized due to the large number of records. It is estimated that the topic of this article may lead to greater interest in the preservation of institutional photographic collections, resulting in even more careful attention to management and storage issues.
Keywords: photographic collections; photography; memory; institutional memory